The Optimal Design of Communication Module for Campus Smart Card - Zhu Lin (Institute of Advanced Engineering and Science, 2014)
Campus Card is an important part in the digital campus life. However, due to the problems of current network design, in the course of card using, the signal channels are seized by a large number of communication tags, which leads to the phenomena of blocked communication process and unsmooth communication. In order to solve this problem, the communication module of card system has been optimized in this paper. The module consists of two parts, which are writing system and reading system. A multi-tasking multi-point mapping decomposition technique was introduced to the designation of communication module. Using the method based on the combination of Map and Reduce function to make the task decomposition which is from a sudden increase of network traffic characteristics and database, obtain a large number of sub-tasks, and accomplish the management of mutation network traffic. Experimental results show that in the task scheduling of optimized module, the solution time is short and response is fast. It can solve the communication blocked problems in the process of card using. Furthermore, it provides theoretical references for the improvement of communication system design of smart card, and promotes the construction of digital campus evolving. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4251